Beneficial effects of n‐hexane bark extract of Onosma echioides L. on diabetic peripheral neuropathy. Issue 10 (17th May 2019) - Shoaib, Ambreen; Badruddeen,; Dixit, Rakesh Kumar; Ganash, Magdah; Barreto, George; Ashraf, Ghulam Md; Siddiqui, Hefazat Hussain
Abstract: Onosma echioides Linn (Boraginaceae) is the most frequently used curative herb widely used for kidney obstruction, sciatic pain, and gout. The present study was designed to investigate the therapeutic effects of n‐hexane bark extract of O. echioides (OE) L. root in vivo against Streptozotocin‐induced diabetic neuropathy in SD rats. For in vivo activity, the experiment was categorized into five different groups ( n = 5). Group‐I was considered as nondiabetic/normal control (NC) treated with 0.5% carboxymethyl cellulose (CMC), Group II as diabetic control, Group‐III, IV, and V served as diabetic treated with OE 50, OE 100, and pregabalin at a dose of 50, 100, and 10 mg/kg body weight, orally, respectively. Body weight, blood glucose, oral glucose tolerance test, behavioral studies (motor coordination test, thermal hyperalgesia, cold allodynia, locomotor activity, oxidative biomarkers (thio barbituric acid reactive substances [TBARS], superoxide dismutase [SOD], glutathione [GSH], and catalase), and histopathology of the sciatic nerve were performed. Treatment with OE showed a dose‐dependent increase in neuroprotective activity by improving the myelination and decreasing the axonal swelling of nerve fibers. The verdicts of behavioral activities showed a remarkable effect on animals after the treatment of extract and standard drug pregabalin. In conclusion, our findings supported the traditional application of OE and explored its importance in the management of diabetic neuropathy. Additional clinical experiments may provide novel therapeutic drugs for diabetes and its complications. Abstract : n‐Hexane bark extract of Onosma echioides Linn has protective effects. Extract of O. echioides improved behavior and attenuated oxidative stress in streptozotocin‐treated rats. Protection induced by O. echioides might be related to improved myelination and decreased axonal swelling in diabetic rats